The analysis of formation of the labour and enterpriese resource road construction JSC «SLAVIC DRSU - E. A. Golubeva (Вестник СибАДИ, 2017)
The analysis of use of a manpower of the enterprise of road construction of JSC Slavyanskoye DRSU is provided in article. Formation of a manpower at the enterprises of road branch has the specifics. On the basis of the analysis of statistical data in two years conclusions are drawn and recommendations about improvement of personnel policy of the enterprise are offered.